2006
DOI: 10.1016/j.virol.2005.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of nelfinavir-resistant HIV-1 protease and the p1–p6 substrate

Abstract: The selective pressure of the competitive protease inhibitors causes both HIV-1 protease and occasionally its substrates to evolve drug resistance. We hypothesize that this occurs particularly in substrates that protrude beyond the substrate envelope and contact residues that mutate in response to a particular protease inhibitor. To validate this hypothesis, we analyzed substrate and protease sequences for covariation. Using the chi2 test, we show a positive correlation between the nelfinavir-resistant D30N/N8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 13 publications
3
50
1
Order By: Relevance
“…This effect is even more pronounced in subtype AE, where N88S pulls D30 out of the active site (21). We also showed that D30 not only is key for inhibitor binding but also is essential for recognition of the p1-p6 cleavage site (8,15,22). Consequently, the D30N mutation, which lowers affinity for NFV (23), also likely compromises p1-p6 recognition, leading to coevolution of this cleavage site (15).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Protease (Pr)mentioning
confidence: 69%
See 2 more Smart Citations
“…This effect is even more pronounced in subtype AE, where N88S pulls D30 out of the active site (21). We also showed that D30 not only is key for inhibitor binding but also is essential for recognition of the p1-p6 cleavage site (8,15,22). Consequently, the D30N mutation, which lowers affinity for NFV (23), also likely compromises p1-p6 recognition, leading to coevolution of this cleavage site (15).…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Protease (Pr)mentioning
confidence: 69%
“…While some of these mutations may compensate for loss of viral fitness and improve efficiency of Gag processing by the resistant PR (11, 13), we previously found that they may also directly modulate drug resistance (14). Frequently, these mutations arise within the Gag cleavage sites, particularly the NC-p1 and p1-p6 sites (15)(16)(17)(18). Cleavage site mutations have been specifically associated with several major protease resistance mutations (14,16,17), suggesting that as the virus evolves resistance to protease inhibitors with prolonged protease inhibitor therapy, evolution of cleavage sites could be a fairly frequent mechanism for maintaining viral fitness.…”
Section: H Uman Immunodeficiency Virus Type 1 (Hiv-1) Protease (Pr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as is evident from our enzyme kinetics data, the D30N/N88D mutations in clade B will likely affect substrate binding and processing. Several studies have observed substrate coevolution in instances in which the protease mutates active-site residues in order to confer inhibitor resistance (22,23). However, since the AE-N88S protease variant has no active-site mutations, the enzyme retains the ability to effectively recognize substrates while conferring NFV resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic peptides, however, are a poor substitute for the Gag polyprotein in terms of long-range intermolecular interactions and conformational changes that can alter the accessibility of Gag cleavage junctions. Additionally both protease and Gag mutate and coevolve in response to protease inhibitors in current clinical use (10)(11)(12)(13)(14)(15)(16)(17). Primary mutations (i.e., mutations at the catalytic site of protease) and mutations within the Gag cleavage sites are readily amenable to investigation using peptide analogs.…”
mentioning
confidence: 99%